2015
DOI: 10.4103/1008-682x.154307
|View full text |Cite
|
Sign up to set email alerts
|

Zygotic chromosomal structural aberrations after paternal drug treatment

Abstract: In recent years, the field of male-mediated reproductive toxicology has received growing attention. It is now well-established that many drugs, chemicals, and environmental factors can harm male germ cells by inducing DNA damage. Male germ cells have extensive repair mechanisms that allow detection and repair of damaged DNA during the early phases of spermatogenesis. However, during the later phase of spermiogenesis, when the haploid spermatids undergo chromatin condensation and become transcriptionally quiesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Indeed, it has been demonstrated that immotile and even dead spermatozoa, for example, when lyophilized or recovered from frozen cadavers, can produce normal offspring when injected into the same species oocyte [ 3 , 4 ]. On the other hand, the motile spermatozoa with damaged DNA (i.e., after chemotherapy) can fertilize the oocyte but subsequent development is compromised [ 5 ]. Typically, these spermatozoa decondense in the cytoplasm and form pronuclei with delayed DNA replication; further cleavage is abnormal, and micronuclei can be detected in the cytoplasm of the two-cell embryos [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that immotile and even dead spermatozoa, for example, when lyophilized or recovered from frozen cadavers, can produce normal offspring when injected into the same species oocyte [ 3 , 4 ]. On the other hand, the motile spermatozoa with damaged DNA (i.e., after chemotherapy) can fertilize the oocyte but subsequent development is compromised [ 5 ]. Typically, these spermatozoa decondense in the cytoplasm and form pronuclei with delayed DNA replication; further cleavage is abnormal, and micronuclei can be detected in the cytoplasm of the two-cell embryos [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%